Aromatic hydrocarbon macrocycles for highly efficient organic light-emitting devices with single-layer architectures. Issue 2 (17th November 2015) - Xue, Jing Yang; Izumi, Tomoo; Yoshii, Asami; Ikemoto, Koki; Koretsune, Takashi; Akashi, Ryosuke; Arita, Ryotaro; Taka, Hideo; Kita, Hiroshi; Sato, Sota; Isobe, Hiroyuki
Abstract : Aromatic hydrocarbon macrocycles for phosphorescent organic light-emitting devices with a single-layer architecture were designed. Abstract : A modern electrophosphorescent organic light-emitting device (OLED) achieves quantitative electro-optical conversion by using multiple layers of molecular materials designed through role allotment for independent and specific functions. A unique, potentially innovative device architecture, i.e., a single-layer phosphorescent OLED, is currently being developed by designing multirole base materials via a structural combination of multiple functional components in single molecules. The multirole molecules, however, inevitably require multiple processes to synthesize their multiple components and, moreover, to assemble these components synthetically into one molecule. We herein show that the multirole base material for a highly efficient single-layer phosphorescent OLED can be designed and synthesized with a single, very simple aromatic hydrocarbon component of toluene merely through a one-pot macrocyclization. Without requiring the assembly tasks at the synthesis stage, the molecular design allows for a concise one-pot synthesis of, and a quantitative electro-optical conversion in, the single-layer device architecture with a single-component base material.